Policy Implementation of Curriculum Implementation Guidelines in Education Units Under Special Conditions in Madrasah Tsanawiyah Ma'had Al-Zaytun, Gantar District, Indramayu Regency - Adninnafi’ah, Lu’lu; Siswoyo, Mukarto; Agustina, Heriyani (Department of Public Administration, 2023)
The COVID-19 pandemic in Indonesia has caused the government to issue policies to prevent the spread of this pandemic, which affects all sectors in Indonesia, one of which is the education sector. Schools that were originally face-to-face or offline, must be carried out online. This causes the curriculum that has been arranged in such a way, cannot be implemented properly. However, the policy is considered unable to overcome learning loss so it needs to be refined. Therefore, the government has set a policy on Guidelines for Curriculum Implementation in the Framework of Learning Recovery which is more commonly referred to as the Independent Curriculum (Kurikulum Merdeka). This study aims to find out how the policy is implemented in Madrasah Tsanawiyah Ma’had Al-Zaytun, the factors that support its implementation, as well as the factors that hinder it. This research uses a qualitative approach with qualitative descriptive methods. Selection of resource persons using purposive sampling techniques. The result of the research is that the implementation of the policy runs in accordance with the rules that have been set, most of the factors support the running of the policy implementation process, but needs attention in socio-economic conditions and budgeting funds.